2e Journée de réflexion de l'EDT GEPROC Génie des procédés appliqué aux bio-industries, 16 décembre 2009, Faculté universitaire des Sciences agronomiques, Gembloux (Belgique) - Thonart, Philippe; Crine, Michel; Delvigne, Frank (Uliège Library, 2010)
The aim of the Thematic Doctoral School in Process Engineering (EDT GEPROC) is to promote multidisciplinary doctoral research in the various fields of application of process engineering. It is therefore quite logical that the 2nd thematic day of reflection organized by the EDT-GEPROC was devoted to the theme of Process Engineering applied to the bio-industries (agri-food, agrofuels and energy, environment, pharmaceutical industry). This event was held on December 16, 2009 on the site of Gembloux Agro-Bio Tech. It brought together 80 participants from the 4 university institutions that are part of the EDT GEPROC (ULg, UMONS, ULB and UCL). It is important at this level to note also the participation of several representatives of the industrial world. Indeed, the contact between PhD students and the industrial world is one of the objectives of the EDT GEPROC. The following program was spread over half a day Translated with www.DeepL.com/Translator (free version)